An Improvement of Computer Based Test System Based on TCExam for Usage with A Large Number of Concurrent Users - Yunarso Anang; Rahadi Jalu Yoga Utama; Masakazu Takahashi; Yoshimichi Watanabe (EMITTER International Journal of Engineering Technology, 2022)
Computer-based test or assessment has been used widely, especially in the current COVID-19 pandemic, where many schools are conducting distance learning as well as distance examination. The need for a computer or software system to support education is inevitable. A range of solutions, from the free/open source software systems to the paid/proprietary ones have been publicly available. Still, an organization with limited resources prefers to find free or low-budget, while yet demanding reliable solutions. We have reported the use of the computer-based test in a new student recruitment test which is held country-wide. We developed the system based on TCExam, a free and open source computer-based test software, and successfully fulfilled the requirements, but with some tweaks. We found that the TCExam has a performance degradation when used by a large number of examinees concurrently, especially during specific phases during the test. This paper reports the result of our investigation to address the problem and suggests some modifications to the base codes as well as a recommendation of the hardware configuration. We evaluated the modified system in a simulated environment. We successfully achieved up to 56% performance gain using the modified system.